Students’ Mathematical Literacy Skills In Solving Contextual Problems Based On Local Sasak - Asmia Nurullia Hanna; Al Kusaeri; M. Habib Husnial Pardi (Alpatih Harapan Semesta, 2026)
Students' persistently low mathematical literacy skills are often attributed to learning processes that are overly abstract and disconnected from reality. To address this gap, integrating cultural contexts into education is essential. This study aims to analyze students' mathematical literacy skills in solving contextual problems based on the local culture of the Sasak tribe. Employing a descriptive qualitative approach, participants were selected from class VIII-B at MTsN 2 Mataram, involving three subjects representing high, moderate, and low ability categories. Data were collected through essay tests laden with Sasak ethnomathematics (Peresean, Gendang Beleq, and Kain Songket contexts) and in-depth interviews, then analyzed via data reduction, data display, and conclusion drawing. The results indicate that high-ability students can comprehensively formulate, employ, and interpret mathematical problems. Moderate-ability students demonstrate adequate procedural mastery but exhibit weaknesses in symbolic modeling. Conversely, low-ability students experience epistemological obstacles and logical errors starting from the initial formulation stage. The study implies that although Sasak culture functions effectively as cognitive scaffolding, its application necessitates reinforcing fundamental conceptual understanding and implementing differentiated learning approaches.